A cycling and education programme for the treatment of hip osteoarthritis: a quality improvement study. (November 2016) - Wainwright, Thomas W.; Immins, Tikki; Middleton, Robert G.
Abstract: Osteoarthritis of the hip is associated with pain, stiffness and limitations to activities of daily living. The aims of this quality improvement project were to introduce a service developed to promote the self-management of hip osteoarthritis through exercise and education and to assess the impact of the programme on pain, function and quality of life. The service was a six-week cycling and education programme and 119 participants took part. Statistically significant improvements were found for Oxford Hip Scores (Mean (SD) change 4.14, 95%, CI 3.02, 5.25, p < 0.001); Sit-to-stand scores (mean change 3.06, 95%, CI 2.33, 3.79, p < 0.001); EQ5D-5L Utility (mean change 0.06, 95%, CI 0.03, 0.09, p < 0.001); EQ5D VAS (mean change 7.05, 95%, CI 4.72, 9.39, p < 0.001); pain on weight-bearing (WB) (mean change 1.56, 95%, CI 0.77, 2.36, p < 0.001), HOOS function (median change (IQR) 7.35, 1.84 to 19.12, p < 0.001) and TUG test (median change 1.11, 0.31 to 2.43, p < 0.001). Participants reported improvements in pain and function; increased confidence in managing hip pain and an increase in motivation to exercise. These findings were supported by a patient and public involvement forum who suggested extending the programme to eight weeks. These results suggest that the service has potential in the management of hip osteoarthritis.